Polycystic Ovary Syndrome and Mental Health Outcomes in Women of Reproductive Age: A Cross-Sectional Observational Study - Luqman Bin Fahad,; Mahreen Ayesha, (Asian Journal of Pharmaceutical Research and Development, 2026)
Objectives: To evaluate the prevalence and severity of depression, anxiety, perceived stress, and self-esteem impairment in women with PCOS compared to non-PCOS controls, and to examine the moderating roles of area of residence, physical symptom burden, lifestyle risk factors, and coping strategies on psychological outcomes. Design: Cross-sectional observational study conducted over three months (July–September 2025). Interventions: Administration of four validated psychometric instruments: PHQ-9 (depression), GAD-7 (anxiety), PSS-10 (perceived stress), and Rosenberg Self-Esteem Scale (RSES). Main Outcome Measures: PHQ-9, GAD-7, PSS-10, and RSES scores categorised by validated severity cut-offs; Composite Vulnerability Index risk tier; physical symptom burden score. Results: Of 300 participants (155 PCOS, 145 non-PCOS; mean age 25.66 ± 3.99 years), 94.8% of PCOS women had clinically significant depression (PHQ-9 ≥10) versus 34.5% of controls; mean PHQ-9 15.89 ± 3.97 versus 6.59 ± 7.24. Clinically significant anxiety affected 86.5% of PCOS versus 31.7% of non-PCOS women (mean GAD-7 12.83 versus 5.43). Low self-esteem was present in 65.8% of PCOS versus 11.7% of controls. Rural PCOS women had the highest mean depression scores (16.36 ± 2.96). Family history of PCOS (80.6% PCOS prevalence), short sleep (≤5 hrs: 89.8%), and high junk food consumption (3–5x/week: 85.6%) were strongly associated with PCOS. Conclusion: PCOS imposes a profound, multi-dimensional psychological burden encompassing depression, anxiety, stress, and low self-esteem, further exacerbated by rural residence and adverse lifestyle factors. Integrated, PCOS-specific mental health screening and psychosocial intervention are urgently required in clinical practice.